A girl with steroid cell ovarian tumor misdiagnosed as non-classical congenital adrenal hyperplasia - Yılmaz-Ağladıoğlu, Sebahat; Savaş-Erdeve, Şenay; Boduroğlu, Esin; Önder, Aşan; Karaman, İbrahim; Çetinkaya, Semra; Aycan, Zehra (The Turkish Journal of Pediatrics, 2013)
Ovarian steroid cell tumors are rarely encountered in prepubertal girls. The majority of these tumors produce hormones, testosterone being the leading one. These tumors may either coexist with or imitate congenital adrenal hyperplasia (CAH). We present a 13-year-old female patient who was diagnosed with non-classical CAH at six years of age while being investigated for premature pubarche. She was diagnosed with steroid cell ovarian tumor after a delay of six years. The diagnosis was based on radiologic imaging, which was performed to investigate causes of unsuccessful metabolic control while under high-dose steroid therapy. The right ovarian hypoechoic mass of 23x22 mm was excised laparoscopically, preserving the ovary. Immunohistochemical staining showed that tumor cells were strongly positive with inhibin and focally positive with vimentin. Based on these findings, the patient was diagnosed with ovarian steroid cell tumor not otherwise specified. In the postoperative second week, total testosterone level was